2023
DOI: 10.1007/s13346-023-01456-y
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of doxorubicin prodrug via lipid nanocapsule–based hydrogel for the treatment of glioblastoma

Mingchao Wang,
Raphaël Bergès,
Alessio Malfanti
et al.

Abstract: Glioblastoma (GBM) recurrences appear in most cases around the resection cavity borders and arise from residual GBM cells that cannot be removed by surgery. Here, we propose a novel treatment that combines the advantages of nanomedicine and local drug delivery to target these infiltrating GBM cells. We developed an injectable lipid nanocapsule (LNC)–based formulation loaded with lauroyl-doxorubicin prodrug (DOXC12). Firstly, we demonstrated the efficacy of intratumoral administration of DOXC12 in GL261 GBM-bea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…These recurrences arise in 90% of cases along the post-surgical cavity borders and no resolutive treatment succeeds in inhibiting their onset and proliferation 7,8 . We have previously demonstrated that delivering hydrogels loaded with nanomedicines in the post-surgical cavity of GBM is a safe and promising therapeutic approach to kill residual tumor cells in the gap period between surgery and chemoradiation [9][10][11][12][13][14] . For example, the Lauroyl-gemcitabine lipid nanocapsules (GemC 12 -LNC) hydrogel is injectable, well tolerated, has adequate properties for an application in the brain 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recurrences arise in 90% of cases along the post-surgical cavity borders and no resolutive treatment succeeds in inhibiting their onset and proliferation 7,8 . We have previously demonstrated that delivering hydrogels loaded with nanomedicines in the post-surgical cavity of GBM is a safe and promising therapeutic approach to kill residual tumor cells in the gap period between surgery and chemoradiation [9][10][11][12][13][14] . For example, the Lauroyl-gemcitabine lipid nanocapsules (GemC 12 -LNC) hydrogel is injectable, well tolerated, has adequate properties for an application in the brain 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The co-loading of GemC 12 -LNC with other drugs acting on tumor cells or tumor stem cells, such as paclitaxel 12 and salinomycin 15 respectively, provided a synergistic effect in vitro but did not improve the survival of animals (unpublished data) suggesting that killing tumor cells only is not enough. On the contrary, when we combined the local administration of a similar hydrogel (lauroyl-doxorubicin-LNC hydrogel) with the systemic injection of the anti-in ammatory drug ibuprofen the survival of animals was extended 14 suggesting that acting both on tumor cells and on the post-surgical in ammation could lead to a delay in the onset of recurrences. Indeed, the brain response following GBM surgery is characterized by physiological regenerative responses bene cial for the healing process, but also by distinctive timedependent peritumoral immune responses exerting glioma-supportive effects 5,16,17 .…”
Section: Introductionmentioning
confidence: 99%